Odpowiedź :
Odpowiedź:
a) 8 - 4k + 2k - [tex]k^{2}[/tex] = 8 - 2k - [tex]k^{2}[/tex]
b) 10 - 2y + 5x - xy
c) 8[tex]x^{2}[/tex] + 32x -6x -24 = 8[tex]x^{2}[/tex] + 26x - 24
d) -6[tex]m^{2}[/tex] - 6mp + 6mp + 6[tex]p^{2}[/tex] = -6[tex]m^{2}[/tex] + 6[tex]p^{2}[/tex]
zad. 2
2(2y + 3) + 2(4x-2)
zad.3
xy-(x+1)(y-2) = xy - (xy -2x +y - 2) = xy + xy + 2x - y + 2 = 2xy + 2xy -y + 2 =
=2· (-2) · (-3) + 2· ( -2) - (-3) + 2 = 12 + (-4) +3 + 2 = 13
Szczegółowe wyjaśnienie:
Odpowiedź:
Szczegółowe wyjaśnienie:
zad.1
a) (4+k)(2-k)=
8-4k+2k-k^2=
8-2k-k^2
b) (2+x)(5-y)=
10-2y+5x-xy
c) (4x-3)(2x+8)=
8x^2+32x-6x-24=
8x^2+24x-24
d) (-2m+2p)(3m+3p)=
-6m^2-6mp+6mp+6p^2=
-6m^2+6p^2
zad.2
2(2y+3)+2(4x-2)=
4y+6+8x-4=
4y+2+8x
zad.3
xy-(x+1)(y-2)=
xy-xy-2x+y-2=
-2x+y-2
x=-2 y=-3
-2*(-2)+(-3)-2=
4+(-3)-2=
1-2=
-1